Use Profile of Magnesium Sulfate in Anesthesia in Brazil - Cavalcanti, Ismar Lima; Lima, Fernando Lopes Tavares de; Silva, Mario Jorge Sobreira da; Cruz Filho, Rubens Antunes da; Braga, Estêvão Luiz Carvalho; Verçosa, Nubia (Frontiers in Pharmacology, 2019)
Objectives: The use of magnesium sulfate in the perioperative period has several benefits, including analgesia, inhibition of the release of catecholamines and prevention of vasospasm. The aim of this survey was to provide an overview of the use of magnesium sulfate in anesthesia. Method: This was a prospective descriptive cross-sectional study. An online questionnaire was sent to 9869 Brazilian anesthesiologists and trainees. The questionnaire comprised closed questions mainly regarding the frequency, indications, adverse events and doses of magnesium sulfate used in anesthesia. Results: Of the 954 doctors who responded to the survey, 337 (35.32%) reported using magnesium sulfate in anesthesia. The most commonly cited indications for the use of magnesium sulfate in anesthesia were (n/%): postoperative analgesia (245/72.70%), reduction of anesthetic consumption (240 / 71.21%) and prevention and treatment of preeclampsia and seizures in eclampsia (220 / 65.28%). The most frequently reported adverse events were hypotension (187 / 55.48%), residual neuromuscular blockade (133/39.46%), hypermagnesemia (30/8.90%) and intravenous injection pain (26/7.71%). The intravenous doses of magnesium sulfate used in most general anesthesia inductions were between 30 and 40 mg.kg-1. Conclusions: Magnesium sulfate is an important adjuvant drug in the practice of anesthesia, with several clinical indications and a low incidence of adverse events when used at recommended doses.